Decreased number and impaired function of type 1 regulatory T cells in autoimmune diseases. Issue 8 (21st January 2019) - Jia, Xi; Zhai, Tianyu; Wang, Bing; Yao, Qiuming; Li, Qian; Mu, Kaida; Zhang, Jin‐an
Abstract: Type 1 regulatory T (Tr1) cell is a special type of T regulatory cells with surface molecular markers such as lymphocyte‐activation gene 3 and CD49b. A key property of Tr1 cells is the capability to produce high‐level interleukin 10 (IL‐10) upon activation, in a FOXP3‐independent manner. The immunosuppressive function of IL‐10 producing Tr1 cells has been extensively studied for many years. Autoimmune diseases (AIDs) are conditions in which the immune system breaks down and starts to attack the body. AIDs include inflammatory bowel disease, rheumatoid arthritis, multiple sclerosis (MS), type 1 diabetes mellitus, Greaves' disease, and so forth. In recent years, more and more studies have documented that the number of Tr1 cells is decreased and the function is inhibited in a variety of AIDs, among which MS is the most widely studied. The protocol for engineering Tr1 cell therapy has been established and is gradually being used in clinical practice in recent years. Tr1 cell therapy has been proven to be safe and effective, but it is mainly involved in myeloid leukemia, graft versus host disease currently. Its therapeutic role in AIDs still needs to be further explored. In this study, we will summarize the research advances of Tr1 cells in AIDs, which will provide useful information for treating AIDs through Tr1 cell therapy in the future.